Yours for the asking : - Levy, Reynold (John Wiley and Sons, 2008)
Yours for the Asking will greatly enhance your effectiveness and confidence in fundraising. Drawing on his experience in raising over one billion dollars in six years as President of Lincoln Center, Reynold Levy has written the ultimate insider's guide to asking for and receiving funds." "This hands-on guide is written out of a conviction that those charged with the privilege of raising funds can do better. Much better. Filled with countless examples, case studies, sample letters, and illustrative materials, Yours for the Asking will transform your view of fundraising from a dreaded task to a high calling, from "pleading" for money to helping donors find pleasure in advancing social causes and strengthening key nonprofit institutions